2016
DOI: 10.1038/srep38526
|View full text |Cite
|
Sign up to set email alerts
|

RCANs regulate the convergent roles of NFATc1 in bone homeostasis

Abstract: Activation of calcineurin-dependent nuclear factor of activated T cells c1 (NFATc1) is convergent for normal bone homeostasis. NFATc1 regulates both osteoclastogenesis and osteoblastogenesis. Here we investigated the roles of regulator of calcineurin (RCAN) genes in bone homeostasis. RCANs function as potent physiological inhibitors of calcineurin. Overexpression of RCANs in osteoclast precursor cells attenuated osteoclast differentiation, while their overexpression in osteoblasts enhanced osteoblast different… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 38 publications
0
11
0
Order By: Relevance
“…Also, mice deficient in NFATc1 exhibited defects in osteoclast differentiation and demonstrated symptoms of osteopetrosis 52 . Similarly, the inhibition of NFATc1 transcriptional activity attenuated RANKL osteoclastogenesis 53,54 . In the present study, we showed that C-PC significantly inhibited RANKL-induced c-Fos expression at the protein level.…”
Section: Discussionmentioning
confidence: 98%
“…Also, mice deficient in NFATc1 exhibited defects in osteoclast differentiation and demonstrated symptoms of osteopetrosis 52 . Similarly, the inhibition of NFATc1 transcriptional activity attenuated RANKL osteoclastogenesis 53,54 . In the present study, we showed that C-PC significantly inhibited RANKL-induced c-Fos expression at the protein level.…”
Section: Discussionmentioning
confidence: 98%
“…NFATc1 is well known as a master regulator of osteoclastogenesis (Kim et al, 2016) whilst the role of NFATc1 signaling in osteoblasts is not well understood and is still controversial (Kim et al, 2016; Penolazzi et al, 2011). Ca 2+ ‐NFATc1 signaling and NFAT transcriptional activity are previously demonstrated to be activated during rat osteoblastic mineralization by high ATP concentrations acting through P2X7R (Grol et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…46 It is reported that disruption of RCAN2 could lead to reducing bone mass, which is related to increased osteoclast function and reduced osteoblast function. 47 IL9R is associated with hematopoietic cell lineage. 48 Our result indicated that hsa-let-7a-5p and its target (RCAN2 and IL9R) could be involved in osteonecrosis of the femoral head.…”
Section: Discussionmentioning
confidence: 99%